Rapid and Highly Accurate Prediction of Poor Loop Diuretic Natriuretic Response in Patients With Heart Failure. (January 2016) - Testani, Jeffrey M.; Hanberg, Jennifer S.; Cheng, Susan; Rao, Veena; Onyebeke, Chukwuma; Laur, Olga; Kula, Alexander; Chen, Michael; Wilson, F. Perry; Darlington, Andrew; Bellumkonda, Lavanya; Jacoby, Daniel; et al.
Abstract : Background—: Removal of excess sodium and fluid is a primary therapeutic objective in acute decompensated heart failure and commonly monitored with fluid balance and weight loss. However, these parameters are frequently inaccurate or not collected and require a delay of several hours after diuretic administration before they are available. Accessible tools for rapid and accurate prediction of diuretic response are needed. Methods and Results—: Based on well-established renal physiological principles, an equation was derived to predict net sodium output using a spot urine sample obtained 1 or 2 hours after loop diuretic administration. This equation was then prospectively validated in 50 acute decompensated heart failure patients using meticulously obtained timed 6-hour urine collections to quantify loop diuretic-induced cumulative sodium output. Poor natriuretic response was defined as a cumulative sodium output of <50 mmol, a threshold that would result in a positive sodium balance with twice-daily diuretic dosing. Following a median dose of 3 mg (2–4 mg) of intravenous bumetanide, 40% of the population had a poor natriuretic response. The correlation between measured and predicted sodium output was excellent ( r =0.91; P <0.0001). Poor natriuretic response could be accurately predicted with the sodium prediction equation (area under the curve =0.95, 95% confidence interval 0.89–1.0; P <0.0001). Clinically recorded net fluid output had a weaker correlation ( r =0.66; P <0.001) and lesser ability to predict poor natriuretic response (area under the curve =0.76, 95% confidence interval 0.63–0.89; P =0.002). Conclusions—: In patients being treated for acute decompensated heart failure, poor natriuretic response can be predicted soon after diuretic administration with excellent accuracy using a spot urine sample. Abstract : Supplemental Digital Content is available in the text.